In Their Own Words: John E. Burris. (14th April 2021) - Verdier, James M
Abstract: In Their Own Words chronicles the stories of scientists who have made great contributions to their fields. These short histories provide our readers a way to learn from and share their experiences. We will publish the results of these conversations in the pages of BioScience and on our podcast, BioScience Talks (http://bioscienceaibs.libsyn.com ). This history is with John E. Burris, emeritus president of the Burroughs Wellcome Fund. He is also a past president of AIBS. Note: Both the text and audio versions have been edited for clarity and length.